2018
DOI: 10.1139/apnm-2017-0858
|View full text |Cite
|
Sign up to set email alerts
|

Prior treatment with the AMPK activator AICAR induces subsequently enhanced glucose uptake in isolated skeletal muscles from 24-month-old rats

Abstract: 5′ AMP-activated protein kinase (AMPK) activation may be part of the exercise-induced process that enhances insulin sensitivity. Independent of exercise, acute prior treatment of skeletal muscles isolated from young rats with a pharmacological activator of AMPK, 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR), causes subsequently improved insulin-stimulated glucose uptake (GU). However, efficacy of a single prior AICAR exposure on insulin-stimulated GU in muscles from old animals has not been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(67 reference statements)
1
15
2
Order By: Relevance
“…The data presented herein oppose the findings by Fisher et al [ 14 ], though the muscles studied differed with regards to type, species, and gender. However, a recent study reported that prior AICAR stimulation improved insulin sensitivity of rat epitrochlearis muscle in the absence of serum [ 20 ], emphasizing that the discrepancies observed between the present study and that of Fisher et al [ 14 ] are not due to differences in muscle type or species. Since Oki et al [ 20 ] and Fisher et al [ 14 ] investigated muscle from old (24 months-old) and young (likely ~6 weeks-old) rats, respectively, the observed difference could be due to an effect of age somehow affecting the necessity of a serum factor to mediate improvements in muscle insulin sensitivity after prior AICAR stimulation.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The data presented herein oppose the findings by Fisher et al [ 14 ], though the muscles studied differed with regards to type, species, and gender. However, a recent study reported that prior AICAR stimulation improved insulin sensitivity of rat epitrochlearis muscle in the absence of serum [ 20 ], emphasizing that the discrepancies observed between the present study and that of Fisher et al [ 14 ] are not due to differences in muscle type or species. Since Oki et al [ 20 ] and Fisher et al [ 14 ] investigated muscle from old (24 months-old) and young (likely ~6 weeks-old) rats, respectively, the observed difference could be due to an effect of age somehow affecting the necessity of a serum factor to mediate improvements in muscle insulin sensitivity after prior AICAR stimulation.…”
Section: Discussioncontrasting
confidence: 90%
“…However, a recent study reported that prior AICAR stimulation improved insulin sensitivity of rat epitrochlearis muscle in the absence of serum [ 20 ], emphasizing that the discrepancies observed between the present study and that of Fisher et al [ 14 ] are not due to differences in muscle type or species. Since Oki et al [ 20 ] and Fisher et al [ 14 ] investigated muscle from old (24 months-old) and young (likely ~6 weeks-old) rats, respectively, the observed difference could be due to an effect of age somehow affecting the necessity of a serum factor to mediate improvements in muscle insulin sensitivity after prior AICAR stimulation. However, the mice used in the present study were young, suggesting that, at least in mice, the ability for pharmacological AMPK activation to increase skeletal muscle insulin sensitivity in the absence of serum is not restricted to aged muscle.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We therefore determined the GTPase activity of fulllength TBC1D4 protein toward recombinant Rab10 in vitro. Purified GST-Rab10 was loaded with [γ- 32 P]GTP, incubated with purified full-length TBC1D4 protein, and the rate of [ 32 P] phosphate release resulting from hydrolysis of [γ- 32 P]GTP was measured as described previously (7). Figure 2, A and B illustrate that purified GST-Rab10 exhibited some endogenous GTPase activity, but the initial velocity of GTP hydrolysis was substantially increased in the presence of full-length TBC1D4.…”
Section: Tbc1d4 Phosphorylation In Vitromentioning
confidence: 86%
“…Although the difference was subtle, we observed statistically significant differences in the phosphorylation at Ser 704 of AS160 in some cases. Phosphorylation of this site has been reported to be modulated by exercise and its related signals (26,27). In fact, AS160 has several additional phosphorylation sites, and phosphorylation at some of these sites is reported to be sustained after several hours of exercise (28 -32), including Ser 341 as well as Ser 704 (26).…”
Section: Two Rabgaps and Glut4 Releasementioning
confidence: 99%